WRITTEN ENGLISH LANGUAGE TEST IN BLOOM’S TAXONOMY PERSPECTIVE - Moura da Silva, Tatiane (2021)
Considering that educational assessment is much more than a classification process and plays a significant role in the teaching-learning process, this article, with a qualitative approach, aims to analyze, from the perspective of Bloom’s Taxonomy, 11 written tests of the English language applied in 2019, by four teachers from two state schools in União dos Palmares-AL. Bloom’s Taxonomy consists of a classification of the complexity of mental operations enabling the identification of the student’s performance level. Thus, to answer the proposed question, Bloom’s Taxonomy shows itself as an adequate tool, since it allows analyzing and tabulating evaluative questions in cognitive levels of complexity, classifying them in a hierarchy from less to more complex.The results showed that most questions are at the first level of complexity, in which the student only needs to recognize the information.